2015
DOI: 10.15252/embj.201591885
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of adaptor protein 2μ ( AP ‐2μ) in cochlear hair cells impairs vesicle reloading of synaptic release sites and hearing

Abstract: Active zones (AZs) of inner hair cells (IHCs) indefatigably release hundreds of vesicles per second, requiring each release site to reload vesicles at tens per second. Here, we report that the endocytic adaptor protein 2l (AP-2l) is required for release site replenishment and hearing. We show that hair cell-specific disruption of AP-2l slows IHC exocytosis immediately after fusion of the readily releasable pool of vesicles, despite normal abundance of membrane-proximal vesicles and intact endocytic membrane re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
170
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(186 citation statements)
references
References 54 publications
13
170
1
2
Order By: Relevance
“…Next, we moved on to early postnatal injections (Fig A, middle and lower, postnatal day 5–7) into the cochlea via the round window, which had proven highly successful for transduction of hair cells (e.g., Akil et al , ; Jung et al , ). We employed AAV‐PHP.B, a novel AAV serotype (Deverman et al , ) with improved efficiency of neural transduction, for expression of Chronos‐ES/TS and Chronos (hSyn promoter, comparable titers, 10 12 GC/ml) in SGNs.…”
Section: Resultscontrasting
confidence: 99%
“…Next, we moved on to early postnatal injections (Fig A, middle and lower, postnatal day 5–7) into the cochlea via the round window, which had proven highly successful for transduction of hair cells (e.g., Akil et al , ; Jung et al , ). We employed AAV‐PHP.B, a novel AAV serotype (Deverman et al , ) with improved efficiency of neural transduction, for expression of Chronos‐ES/TS and Chronos (hSyn promoter, comparable titers, 10 12 GC/ml) in SGNs.…”
Section: Resultscontrasting
confidence: 99%
“…Recent data from conventional synapses suggests that endocytic membrane retrieval per se does not absolutely require AP‐2 or clathrin, which however are both critically required for SV reformation from endosome‐like vacuoles . In line with results obtained in AP‐2μ‐deficient hippocampal neurons, disruption of AP‐2 does not significantly perturb membrane retrieval at IHC ribbon synapses . Upon strong stimulation, loss of AP‐2 leads to the accumulation of endosome‐like vacuoles, which – together with fewer clathrin‐coated pits as well as reduced counts of ribbon‐attached SVs (i.e., at the distal part of the ribbon) – indicates a requirement of AP‐2 for SV reformation.…”
Section: Exocytosis–endocytosis Coupling At Ihc Ribbon Synapsessupporting
confidence: 68%
“…Upon strong stimulation, loss of AP‐2 leads to the accumulation of endosome‐like vacuoles, which – together with fewer clathrin‐coated pits as well as reduced counts of ribbon‐attached SVs (i.e., at the distal part of the ribbon) – indicates a requirement of AP‐2 for SV reformation. Intriguingly, upon prolonged stimulation, the number of membrane‐proximal SVs is unaltered; however, the speed of exocytosis decreases significantly in the mutants, suggesting impaired release site clearance that prevents the membrane‐proximal SVs to reach fusion competence . Otoferlin levels in AP‐2‐deficient IHCs are dramatically reduced and there is an indication that the remaining otoferlin might be more strongly present on the plasma membrane.…”
Section: Exocytosis–endocytosis Coupling At Ihc Ribbon Synapsesmentioning
confidence: 98%
“…Furthermore, Peterson et al () found that this model does not readily account for the serial ISI correlations in ANF spontaneous spike trains and their dependence on mean ISI. More recently, Jung et al () suggested that a gamma contribution might arise if two slow transitions, rather than one, existed in the work cycle of a presynaptic vesicle (involving, e.g., vesicle release, release site clearance, and refilling). It is unclear how well such a model can reproduce empirical ISI distributions and whether it accounts for serial ISI correlations and spike‐count statistics, including their dependence on mean ISI.…”
Section: Models Of Anf Spontaneous Activitymentioning
confidence: 99%